2022
DOI: 10.1123/jtpe.2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Examining Marginality, Isolation, and Emotions and Their Relationship With Physical Educator Intrapersonal Job Beliefs

Abstract: Purpose: Marginality and isolation have been found to negatively impact physical educators. Despite a significant body of research, few studies have included important personal attributes like teacher emotions. The purpose of this study was to examine relationships of teacher marginality, isolation, and emotions (enjoyment, anger, and anxiety) with intrapersonal job beliefs (turnover intention, perceived accomplishment, and organizational commitment). Methods: Physical educators (N = 227; 51% female) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…This is one indicator of the marginality status of PE in the school system. The status of second class subject (Banville, 2015;Hendry, 1975;Kougioumtzis et al, 2011Raymond, 2016 enforced on physical education (and therefore on PE teachers) and unfavourable social perceptions can prompt PE teachers to feel devalued (Raymond, 2016;Simonton et al, 2021). As a result, peer perception is an underlying factor in teachers' professional identity formation.…”
Section: Identity Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one indicator of the marginality status of PE in the school system. The status of second class subject (Banville, 2015;Hendry, 1975;Kougioumtzis et al, 2011Raymond, 2016 enforced on physical education (and therefore on PE teachers) and unfavourable social perceptions can prompt PE teachers to feel devalued (Raymond, 2016;Simonton et al, 2021). As a result, peer perception is an underlying factor in teachers' professional identity formation.…”
Section: Identity Transformationmentioning
confidence: 99%
“…Evidence suggests that both isolation and marginalisation have detrimental effects on the work of PE teachers (Richards et al, 2014). As a result of the subject's marginalised status in many school contexts, PE teachers often feel like second-class teachers or that their contributions to the main goal of their educational institutions are less significant (Gaudreault et al, 2016a), which can have a damaging influence on assessment of one's teaching abilities and emotions, influencing views about being a teacher (Simonton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the less connected a teacher feels in their school, the more likely they are to experience anxiety when teaching. Previous research has also shown strong connections between teacher anxiety and anger in early career education professionals (Skaalvik and Skaalvik, 2011;Simonton et al, 2022;Toropova et al, 2021). These findings suggest that new teachers likely have not developed strong connections to their peers and school community, leaving them more susceptible to anxiety and overall reduced feelings of mattering in their profession (feeling more marginalized; Simonton et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, a secondary purpose related to understanding direct relations to resilience via teacher emotions and indirect impact of environmental views of mattering. This work aims to build upon previous literature that has examined these constructs independently (Richards et al, 2017(Richards et al, , 2018bSimonton et al, 2022) and will allow for a better understanding of the Teacher Well-being and Commitment Model as well as the EDST within the PE context. Specifically, the following hypotheses were tested (See Figure 3): H1: PEM will be positively related with TEM and positive perceptions of mattering overall will be related to higher teacher enjoyment scores while negative views of mattering will be related to higher reported feelings of anger and anxiety.…”
Section: Purpose and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation